Acquired immunity mechanisms in sheep infected with Nematodirus oiratianus: key genes and host responses - Hou, Bin; Su, Rina; Suyala, Dalai; Xu, Li; Zhao, Ruiyuan; Hao, Puguo; Wang, Yali; Mao, Fei; Wu, Bo; Ding, Xuedong; Han, Runqing; Peng, Xuesong; et al. (Frontiers in Veterinary Science, 2025)
BackgroundControlling gastrointestinal nematode infections poses a major challenge in intensive farming, worsened by rising anthelmintic resistance. Developing innovative control strategies is critical. Sheep acquired immunity to Nematodirus oiratianus offers a valuable model for dissecting host-nematode interactions, though underlying immune mechanisms remain unclear.MethodsThis study employed multi-omics analyses (transcriptome and proteome) of lamb duodenum across infection stages, validated by RT-qPCR, iELISA, histopathological staining (HE), and electron microscopy.Results and conclusionsInfection triggered early immune activation mediated by intestinal epithelial cells. Key differentially expressed genes included CLDN18, CCL19, FGB, and Muc5ac, potentially linking to parasite expulsion. Early-stage pathway enrichment in cancer, chemokine signaling, and phagosome function enhanced intestinal barrier integrity and immune cell recruitment. Late-stage upregulation of CCL chemokines directly impacted nematode survival. Intestinal villi shedding was also correlated with parasite clearance. These findings unravel potential mechanisms of acquired immunity against Nematodirus oiratianus, highlighting novel therapeutic targets (e.g., epithelial barrier regulators, chemokine networks) and vaccine candidates for nematode control in livestock.